Identification of a Novel Immunodominant HLA-B*07: 02-restricted Adenoviral Peptide Epitope and Its Potential in Adoptive Transfer Immunotherapy. Issue 7 (September 2015) - Günther, Patrick S.; Peper, Janet K.; Faist, Benjamin; Kayser, Simone; Hartl, Lena; Feuchtinger, Tobias; Jahn, Gerhard; Neuenhahn, Michael; Busch, Dirk H.; Stevanović, Stefan; Dennehy, Kevin M.
Abstract : Adenovirus infections of immunocompromised patients, particularly following allogeneic hematopoietic stem cell transplantation, are associated with morbidity and mortality. Immunotherapy by adoptive transfer of hexon-specific and penton-specific T cells has been successfully applied, but many approaches are impeded by the low number of HLA class I-restricted adenoviral peptide epitopes described to date. We use a novel method to identify naturally presented adenoviral peptide epitopes from infected human cells, ectopically expressing defined HLA, using peptide elution and liquid chromatography-mass spectrometry analysis. We show that the previously described HLA-A*01:01-restricted peptide epitope LTDLGQNLLY from hexon protein is naturally presented, and demonstrate the functionality of LTDLGQNLLY-specific T cells. We further identify a novel immunodominant HLA-B*07:02-restricted peptide epitope VPATGRTLVL from protein 13.6 K, and demonstrate the high proliferative, cytotoxic, and IFN-γ-producing capacity of peptide-specific T cells. Lastly, LTDLGQNLLY-specific T cells can be detected ex vivo following adoptive transfer therapy, and LTDLGQNLLY-specific and VPATGRTLVL-specific T cells have memory phenotypes ex vivo. Given their proliferative and cytotoxic capacity, such epitope-specific T cells are promising candidates for adoptive T-cell transfer therapy of adenovirus infection.